2019
DOI: 10.2147/ijn.s197824
|View full text |Cite
|
Sign up to set email alerts
|

<p>Biomimetic piezoelectric nanocomposite membranes synergistically enhance osteogenesis of deproteinized bovine bone grafts</p>

Abstract: Purpose: The combination of a bone graft with a barrier membrane is the classic method for guided bone regeneration (GBR) treatment. However, the insufficient osteoinductivity of currently-available barrier membranes and the consequent limited bone regeneration often inhibit the efficacy of bone repair. In this study, we utilized the piezoelectric properties of biomaterials to enhance the osteoinductivity of barrier membranes. Methods: A flexible nanocomposite membrane mimick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…While some studies indicated that YAP activation enhances osteogenesis, other studies reported contrary results. In two separate studies by our research group, we found that YAP activation in rat bone marrow-derived MSCs is associated with osteogenesis (Bai et al, 2019;Wei et al, 2019). Pan et al (2018) demonstrated that conditional knockout of YAP expression by the osteoblast lineage in mice reduced osteogenic differentiation and cell proliferation, but promoted adipocyte formation, which in turn led to trabecular bone loss.…”
Section: Role Of Yap/taz In Stem Cell Self-renewal and Maintenance Ofmentioning
confidence: 96%
See 3 more Smart Citations
“…While some studies indicated that YAP activation enhances osteogenesis, other studies reported contrary results. In two separate studies by our research group, we found that YAP activation in rat bone marrow-derived MSCs is associated with osteogenesis (Bai et al, 2019;Wei et al, 2019). Pan et al (2018) demonstrated that conditional knockout of YAP expression by the osteoblast lineage in mice reduced osteogenic differentiation and cell proliferation, but promoted adipocyte formation, which in turn led to trabecular bone loss.…”
Section: Role Of Yap/taz In Stem Cell Self-renewal and Maintenance Ofmentioning
confidence: 96%
“…Other adult stem cells in which YAP plays an integral role in self-renewal and maintenance of the "stemness" phenotype include neural stem cells (Han et al, 2015;Bao et al, 2017), muscle satellite cells (Judson et al, 2012), and intestinal stem cells (Imajo et al, 2015;Kim H. B. et al, 2017). These will be discussed in greater detail in sections "Role of YAP/TAZ in Neurogenesis and Neuroregeneration, " "Role of YAP/TAZ in Myogenic Differentiation and Skeletal Muscle Regeneration, " and (Hong et al, 2005;Suh et al, 2012Suh et al, , 2014Yang et al, 2013;, the role of YAP in osteogenic differentiation is controversial (Seo et al, 2013;Sen et al, 2015;Pan et al, 2018;Zhu W. Q. et al, 2018;Bai et al, 2019;Lin et al, 2019;Wei et al, 2019). The role of TAZ in the osteogenesis of MSCs was first reported by Hong et al (2005), who found that TAZ co-activates gene transcription by RUNX2, an upstream regulator of osteogenesis, while at the same time repressing gene transcription by PPARγ that directs murine bone marrow MSCs into the adipocyte lineage.…”
Section: Role Of Yap/taz In Stem Cell Self-renewal and Maintenance Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Bio-Oss®, a deproteinized bovine bone, has been applied in clinical bone transplantation due to its osteoconductive activity. Nevertheless, Bio-Oss® is extracted from cancellous bone, which makes it not optimal for repairing dense bone defects 41. Therefore, development of biocompatible and biodegradable artificial bone substitutes capable of BMSCs recruitment and osteogenic differentiation is highly desired.…”
Section: Discussionmentioning
confidence: 99%